Problem-based learning of process systems engineering and process integration concepts with metacognitive strategies: The case of P-graphs for polygeneration systems - Promentilla, Michael Angelo B. (Animo Repository, 2017)
Problem-based Learning (PBL) is regarded by many education experts as superior to the traditional lecture, particularly for learning higher-order skills and concepts. PBL can be further reinforced through the utilization of metacognitive skills on the part of the students. Such approaches are particularly useful in Process Systems Engineering (PSE) and Process Integration (PI), where proficiency in the use of methodologies for problem-solving is paramount. In this paper, we describe how such educational strategies can be used to improve learning outcomes through the use of the process graph (P-graph) framework for the synthesis of polygeneration systems, in addition to conventional approaches using lectures and drills. Practical pedagogic implications are then discussed for potential use in teaching related topics in PSE/PI. © 2017 Elsevier Ltd